Macht in der Schule Wissen - Sichtweisen - Erfahrungen. Texte in Leichter Sprache, Einfacher Sprache und Fachsprache - Leonhardt, Nico; Goldbach, Anne; Staib, Lucia; Schuppener, Saskia (Verlag Julius Klinkhardt, 2023)
With a diversity-sensitive and discrimination-critical view, the anthology addresses the significance of power relations within school cultures, structures, and practices. A variety of perspectives are presented in plain and simple language as well as in specialized language. The texts by authors with very different experiences of inclusion and exclusion in the field of education provide stimuli for reflection for lecturers and students in the context of teacher education, practicing teachers, (former) students, and all other interested parties. The volume is intended to encourage readers to engage in (language-)barrier-sensitive reflection and exchange on issues of power in the context of inclusive school development.